Cystic partially differentiated nephroblastoma in a 74‐year‐old patient. Issue 6 (19th August 2021) - Hayashida, Michikata; Nagamoto, Shoichi; Yano, Akihiro; Fu, Takayoshi; Tanaka, Naoto; Hagiwara, Kiichi; Oka, Suguru; Sakaguchi, Kazushige; Kinowaki, Keiichi; Urakami, Shinji
Abstract : Introduction: Cystic partially differentiated nephroblastoma is a multilocular cystic variant of Wilms tumor that always presents in children. However, we encountered an elderly patient with cystic partially differentiated nephroblastoma. Therefore, we report it. Case presentation: A 74‐year‐old male presented with a left renal tumor detected with ultrasonography. Contrast‐enhanced computed tomography and magnetic resonance imaging revealed a 4 cm multilocular cystic tumor with septa, which suggested multilocular cystic renal cell carcinoma. Therefore, we performed a radical nephrectomy. The definitive diagnosis of cystic partially differentiated nephroblastoma was made with histopathological findings. After the surgical resection, no recurrence has occurred in the past 13 years. Conclusion: Cystic partially differentiated nephroblastoma can develop in adults, regardless of age. Furthermore, surgical resection can be used as an established treatment option in adult cystic partially differentiated nephroblastoma cases.